Employee Privacy dan Hostility Between Teams terhadap Employee Performance - Yuliza, Yuliza; Rusdi, Rusdi; Harmen, Hamdi; Hidayat, Muhammad Rahmat (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
This study aimed to identify factors influencing the lack of privacy and the prevalence of gossip in the Kantor Bank Aceh Syariah Cabang Blangpidie. The Structural Equation Modeling (SEM) with Partial Least Squares (PLS) approach was used to analyze data from 103 respondents using The Durkee Hostility Inventory (DHI) as the measurement tool. The results revealed that two constructs, Guilt (feelings of guilt) and Negativism (tendency for negative thinking or rejection), significantly influenced the levels of privacy violation and gossip in the workplace. These findings offer valuable guidance to management in developing more effective strategies to foster a harmonious work environment and mitigate the negative impact of privacy violation and gossip in the workplace.